A study of teacher prediction and student performance - J, Bharath Raj (Journal of All India Institute of Speech and Hearing, 1972)
It is generally assumed that the teacher is a good Predictor of the success or failure of his students in the examination. A scientific enquiry into this problem would be of interest. The question is whether the teacher by virtue of his experience and close contact with the student would be a good judge or good predictor? And if so, how accurate will his Predictions be?